(untitled) (Velocity: Journal of Sharia Finance and Banking, 2025)
This study aims to determine whether there is a difference in the average abnormal return on BUMN work sector companies indexed on the IDX-MES BUMN before and after the ratification of the Nusantara National Capital City Law on 18 January 2022. This research belongs to the type of event study and the data used in this study is secondary data in the form of stock price data. With a sampling technique using purposive sampling method, 8 BUMN and supporting work sector companies were obtained as research samples. This study uses an observation period of 11 effective market working days, namely 5 days before the event, 1 day during the event, and 5 days after the ratification of the IKN Law. Meanwhile, the estimation period used is for 120 effective market working days. The tests carried out are one sample t-test and paired sample t-test, if the data is normally distributed and if it is not normal then use the Wilcoxon signed ranked test. The results showed that the event of the ratification of the IKN Nusantara Law had an impact on investor reactions. Before the ratification, investors tended to react negatively, resulting in a negative and significant abnormal return. However, after there was certainty from the government regarding the IKN development project which would collaborate with the BUMN work sector, investors reacted positively and flocked to invest in BUMN work and support sector stocks.